2020
DOI: 10.3390/foods9111703
|View full text |Cite
|
Sign up to set email alerts
|

Cyclospora Cayetanensis—Major Outbreaks from Ready to Eat Fresh Fruits and Vegetables

Abstract: Cyclospora cayetanensis is a coccidian protozoan that causes cyclosporiasis, a severe gastroenteric disease, especially for immunocompromised patients, children, and the elderly. The parasite is considered as an emerging organism and a major contributor of gastroenteritis worldwide. Although the global prevalence of cyclosporiasis morbidity and mortality has not been assessed, global concern has arisen since diarrheal illness and gastroenteritis significantly affect both developing countries and industrialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Although C. cayetanensis shows a worldwide distribution [ 2 ] with an estimated global average prevalence of 3.55% [ 7 ], primary areas of endemicity comprise resource-poor countries with limited or poor hygiene standards [ 2 ]. In those regions, foreigners, children, elderly, and immunocompromised individuals are particularly frequently diagnosed with cyclosporiasis, while returning travelers are affected in non-endemic areas without relevant effects of sex or age [ 2 , 12 , 13 , 14 ]. In particular, individuals with low socio-economic status are at risk of getting infected with C. cayetanensis [ 15 , 16 ] as impressively indicated by a prevalence of 22.2% in slum dwellers in South Chennai, India [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although C. cayetanensis shows a worldwide distribution [ 2 ] with an estimated global average prevalence of 3.55% [ 7 ], primary areas of endemicity comprise resource-poor countries with limited or poor hygiene standards [ 2 ]. In those regions, foreigners, children, elderly, and immunocompromised individuals are particularly frequently diagnosed with cyclosporiasis, while returning travelers are affected in non-endemic areas without relevant effects of sex or age [ 2 , 12 , 13 , 14 ]. In particular, individuals with low socio-economic status are at risk of getting infected with C. cayetanensis [ 15 , 16 ] as impressively indicated by a prevalence of 22.2% in slum dwellers in South Chennai, India [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit and vegetables are principal components of a healthy diet and have been in high demand in recent years, although eating fresh, minimally processed food is not without risk. Since 1995 until now, major outbreaks of C. cayetanensis infection from fresh produce occurred in USA, Canada and Mexico, linked to the fresh produce originated from endemic countries ( Hadjilouka and Tsaltas, 2020 ). From approximately 1100 globally reported outbreaks where etiological agent was identified, 4.5% were caused by parasites ( Ramos et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclospora cayetanensis is a coccidian protozoan that causes severe gastroenteritis in both immunocompetent and immunocompromised individuals [1,2]. The oocysts of C. cayetanensis are round-oval in shape and 8-10 μm in diameter, and they are not sporulated when excreted in faeces.…”
Section: Introductionmentioning
confidence: 99%
“…The oocysts of C. cayetanensis are round-oval in shape and 8-10 μm in diameter, and they are not sporulated when excreted in faeces. As a result, infection does not spread from personto-person; rather, infection occurs through ingestion of infected oocysts and of contaminated water and food [2,3]. It has been reported that in recent years C. cayetanensis has caused foodborne outbreaks in the United States, Canada and Korea, and these outbreaks were associated with tourists and imported products [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%